PENERAPAN METODE SAW (SIMPLE ADDITIVE WEIGHTING) UNTUK MENENTUKAN SISWA BERPRESTASI (STUDI KASUS PADA SMP NEGERI 24 JAKARTA) - Asep Ramdhani Mahbub; Muhammad Khaerudin; Isti Kharoh (Fakultas Ilmu Komputer dan Desain - Unsurya, 2022)
Decision-making will always be faced and must be done if we are in the scope of management, this is also faced by the management of SMP Negeri 24 Jakarta. Decisions in determining outstanding students are often faced with conditions that can make the decision seem disproportionate, given the many factors and criteria that determine the decision, so we need a computational method that can assist the management in the decision-making process. SAW (Simple Additive Weighting) is a method that selects the best alternative from a number of alternatives based on determined criteria by ranking to find out the highest to lowest value. The recommended results based on the SAW method are students with the highest score, namely 0.9987 for the 6th alternative (A6), which has the highest score above the scores of other students.Â Keywords: dss, achievement, student, saw